Single-Polarization Single-Mode Photonic Crystal Fibers With Uniformly Sized Air Holes - Lu, Dunke; Fang, Xiaohui; Li, Xiaohang; Li, Zhiwei (Journal of lightwave technology, 2021)
We propose a novel design of photonic crystal fiber to achieve the single-polarization single-mode transmission. The topology of this design only employs, with a view of simplicity and stability, uniformly sized circular air holes, and they are all regularly latticed in a pure-silica background. Guiding properties are studied by use of the full-vector finite element method, combined with perfectly matched layers as absorbing boundary conditions. It has been found that, increasing the hole-to-pitch ratio can be performed to broaden the SPSM band, however, subject to a qualification that the ratio should be inadequate to open a bandgap. In addition, influences of the ring number and the inner cladding coverage on transmission characteristics have been thoroughly investigated. An optimized sample is deliberately designed to offer an SPSM band with width of 120 nm, centered at \\boldsymbol \lambda = 1.55 μm. Moreover, the proposed design demonstrates low confinement loss, high nonlinear coefficient, as well as excellent bending resistance.